Detection of Porcine DNA in gelatin containing muffins using Porcine Gene ChipTM analysis - Nursheila Mustafa Muin; Sahilah Abd. Mutalib; Aishah Elias; Norrakiah Abdullah Sani; Aminah Abdullah; Razalee Sedek; Izhar Ariff Mohd. Kashim (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study was carried out to compare the sensitivity of two detection techniques using conventional polymerase chain reaction (PCR) and Porcine gene chip (OliproTM, Selangor, MY). Experimental samples consist of 15 muffins added with different percentage of porcine gelatin (1, 0.5, 0.1, 0.05, 0.01 and 0% w/w), and then cooked in two different ways (steamed and baked) were analyzed for the presence of porcine DNA in gelatin. Both Porcine gene chip and PCR analysis were targeting the gene of cytochrome b (cyt b). Porcine DNA detection in muffin samples using gene chip and PCR method were able to detect the presence of the porcine DNA at 73 and 53% of samples, respectively. Thus, this study demonstrated that the sensitivity level of porcine the DNA detection was high in Porcine Gene chip in comparisons with the PCR analysis.